The effect of styrene-butadiene-rubber/montmorillonite modification on the characteristics and properties of asphalt - Zhang, B.; Xi, M.; Zhang, D.; Zhang, H.; Zhang, B.
In order to study the effect of styrene-butadiene-rubber/montmorillonite (SBR/MMT)modification on the characteristics and properties of asphalt, modified asphalts were prepared by incorporating MMT into SBR and mixing this into asphalt. The X-ray diffraction (XRD)results show that SBR/MMT composites may form an intercalated structure and SBR/MMT modified asphalts may form an exfoliated structure. The morphologies of the samples have been characterized by fluorescent microscopy. The results indicate that SBR/MMT modified asphalts formed an ideal fine network structure. The addition of SBR/MMT to asphalt increased both the softening point and viscosity and decreased the penetration of the modified asphalts at high temperatures. High-temperature storage stability tests indicated that the modified asphalts are very stable in some SRB/MMT, SBR/MMT content range. Especially, the modified asphalts exhibited higher complex modulus (G*)and lower damping factor (tan d). It implies that SBR/MMT displays improved viscoelastic properties, resulting in enhancing its resistance to rutting at high temperature.
Keywords: SBR/MMT; MODIFIED ASPHALTS; MORPHOLOGY; RHEOLOGY; STORAGE STABILITY